2014
DOI: 10.1177/1932296814554260
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia Prediction Using Machine Learning Models for Patients With Type 2 Diabetes

Abstract: Hypoglycemia is a significant adverse outcome in patients with type 2 diabetes and has been associated with increased morbidity, mortality, and cost of care.1 In addition, hypoglycemia is a major limiting factor for the optimization of insulin therapy. In patients with frequent self-monitored blood glucose (SMBG) measurements or those who employ continuous glucose monitors, statistical methods may be used to predict hypoglycemia. For example, Rodbard found that hypoglycemia risk can be estimated using mean, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 6 publications
2
91
0
2
Order By: Relevance
“…Prediction performance improved for temporal and non-temporal models as the observation window size increased with peak performance occurring between 2 and 3 years of patient data [19]. In a different study, significant differences in the accuracy of hypoglycemia prediction using machine learning models for patients with type 2 diabetes were observed as a function of data density (number of self-monitored blood glucose data points) and prediction window size (1 hour to 24 hours) [20]. Model performance increased with denser data and with smaller prediction window size.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction performance improved for temporal and non-temporal models as the observation window size increased with peak performance occurring between 2 and 3 years of patient data [19]. In a different study, significant differences in the accuracy of hypoglycemia prediction using machine learning models for patients with type 2 diabetes were observed as a function of data density (number of self-monitored blood glucose data points) and prediction window size (1 hour to 24 hours) [20]. Model performance increased with denser data and with smaller prediction window size.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that DM complications are far less common and severe in people with well-controlled blood glucose levels. Many of those complications have been studied through machine learning and data mining applications [78], [79], [80], [81], [82], [83], [84], [85], [87], [88], [89], [90], [92], [94], [95], [96], [97].…”
Section: Dm Through Machine Learning and Data Miningmentioning
confidence: 99%
“…Machine learning methods, such as Random Forest, support vector machines (SVM), k-nearest neighbor, and naïve Bayes, were used by Sudharsan B et al [94] to predict hypoglycemia among patients with T2D, whereas support vector regression was used by Georga et al [95] for the same reason. Moreover, a comparison of already published algorithms was reported by Jensen [96] in the same framework.…”
Section: Dm Through Machine Learning and Data Miningmentioning
confidence: 99%
“…Sudharsan et al [112] showed that the detection of hypo-and hyperglycemic events for patients with T2DM is achievable with high accuracy, even if only sparse blood glucose values based on self-monitored blood glucose (SMBG) readings once or twice a day are available. They trained the model with data from approximately 10 weeks.…”
Section: Data-driven Blood Glucose Predictionmentioning
confidence: 99%